Investor Myopia and CEO Turnover. (16th May 2018) - Goyal, Vidhan K.; Low, Angie
Abstract: We find that Chief Executive Officer (CEO) turnover is significantly higher and considerably less sensitive to performance in firms with short investor horizons. Decisions to dismiss a CEO lead to worse operating performance, which is even poorer when investors have short horizons. Furthermore, new managers respond to investor short‐termism by increasing industry‐adjusted capital expenditures while maintaining R&D and patenting activity. In addition, in firms with short‐horizon investors, total risk increases around forced CEO turnovers, largely because of an increase in idiosyncratic risk. The evidence is consistent with short‐term investors distorting corporate policies of firms through their influence on top management turnover.